Prevalence and evolution of helmet use in motorcycle riders in an Argentine city (Mar del Plata, 2006-2014) - Jeremías David Tosi; Ruben Daniel Ledesma; Fernando Martín Poó; Silvana Andrea Montes; Soledad Susana López (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2016)
Traffic collisions involving motorcyclists are a growing problem in low and middle income countries. Helmet use is the foremost protective measure for this group of road users, however many riders do not wear them. The objective of the present study is to report the changes in helmet use during the period 2006-2014 in an Argentine city and discover associated factors for the year 2014. The sample includes more than 6,900 observations of motorcyclists carried out during the years 2006 (n=962), 2008 (n=977), 2012 (n=2,542), and 2014 (n=2,466). The data indicates a progressive increase in helmet use over time, but differences due to gender and type of rider remain. Factors associated to helmet use in motorcycle drivers during 2014 were: passenger helmet use, motorcycle type, license plate use and gender. Although the results are positive, it is necessary to be attentive to the negative consequences of the growing fleet of motorcycles.